Networks, resources and agencies: On the character and production of enabling places - Duff, Cameron (2011)
The study of therapeutic landscapes, restorative places and enabling environments - what might collectively be referred to as enabling places - has revealed much of the relationship between place and health promotion. However, it is arguable that this work has only partially accounted for the diverse therapeutic features of enabling places and the various means of their production. Drawing on Bruno Latour, this paper introduces a conceptual logic of enabling places grounded in the analysis of enabling resources. Three categories of enabling resources will be considered: social, affective and material resources. It will be argued that enabling places are composed in diverse actor-networks, facilitating access to enabling resources and supporting the development of novel agencies or capacities. This draws attention to the various networks and associations that promote health and wellbeing, as well as the resources and agencies necessary to maintain these states. The paper concludes that the analysis of enabling resources, and the networks and agencies that comprise them, provides a novel basis for describing the character and production of enabling places, as well as the diverse benefits associated with them. © 2010 Elsevier Ltd.